Compatibility study between IMT and inter-satellite service systems in 25.25～27.5 GHz frequency band - Zhaojun QIAN; Tan WANG; Long KANG; Bo LI (Dianxin kexue)
Based on the existing technical parameters, the interference coexistence of 25.25～27.5 GHz band international mobile communication（IMT）system and inter-satellite service data relay satellite（DRS）were studied. Based on the aggregate interference assessment, the interference between IMT base station（BS）and inter-satellite service DRS receiver where the DRS orbit at 59 degree, 85 degree and 113 degree longitude were comparatively studied. In addition, the tradeoff between the total number of IMT BS and its transmission power was analyzed with certain interference margin.These results are useful for designing and deployment of IMT systems in 25.25～27.5 GHz band 5G spectrum planning in the future.